A study on the impact of shadow-cast and tree species on in-canyon and neighborhood's thermal comfort. (April 2017) - Morakinyo, Tobi Eniolu; Kong, Ling; Lau, Kevin Ka-Lun; Yuan, Chao; Ng, Edward
Abstract: Tree-planting is one of the veritable tools for combating urban heat island and improving thermal comfort in the wake of global warming and urbanization. However, trees of different species and morphological properties have variable solar attenuation capacity and consequently, thermal comfort regulation potential. Besides, the shadow-cast effect by buildings helps in reducing pedestrian radiant load and consequently improves thermal comfort especially in high-density cities even though ventilation is reduced. Therefore, a holistic and contextual understanding of tree-planting and shadow-casting can help in designing climate-proof cities. In this study, we employed the ENVI-met model to better understand the interaction between these two forms of shading (trees and buildings) on the pedestrians' thermal comfort in Hong Kong and the influence of one over the other. The impact of different urban densities on the thermal comfort improvement potential by eight (8) common tree-species in Hong Kong was specifically studied. Results show that shallow canyons are susceptible to worse thermal condition when compared to their deeper counterparts with similar aspect ratio value. Of all tree configuration parameters, leaf area index, tree height and trunk height are most influential in improving and aggravating daytime and nighttime thermal comfort, respectively. We also found that trees' effectiveness in improving daytime thermal comfort reduces with increasing urban density and vice-versa for nighttime. For the reference of planners and landscape architects, this study recommends tall trees of low canopy density with high trunk in deeper canyons and vice-versa for shallow canyons and open-areas. Highlights: Worsened thermal condition was observed in shallow than deeper canyons of similar aspect ratio value at mid-day. The impact of shadow and tree shading on daytime and nighttime thermal conditions is determined by different mechanisms. The efficacy of trees in improving daytime thermal comfort reduces with increasing urban density. Tall trees of low leaf density and high trunk are proposed for deep canyons and reverse for shallow canyons and open-areas. Hong Kong's Greening Master Plan can be updated using tree-species selection based on urban density mapping.